Redefining coronary revascularization: The emergence of totally endoscopic robotic bypass surgery - Hamad Abdullah Shehab; Syed Mohammad Hussaini; Ibrahim Alabid; Wasim Iyad Alghoul; Mohamedanas Mohamedfaruk Patni (Technology and Health Care, 2026)
Abstract Totally endoscopic coronary artery bypass (TECAB) is regarded as the most advanced minimally invasive surgical coronary revascularization approach. The objective of this review is to discuss the current evidence on the feasibility, safety, clinical outcomes, and implementation challenges of TECAB, and to investigate whether TECAB can be considered a reproducible and effective alternative to traditional and other minimally invasive approaches for coronary artery bypass. A narrative review was conducted of studies reporting perioperative outcomes, graft patency, conversion rates, learning curves, and institutional experience. Available observational series suggest that TECAB can be performed safely in carefully selected patients at experienced centers, with low perioperative mortality, low complication rates, reduced surgical trauma, and shorter length of stay than conventional CABG in selected comparisons. Conversion to open procedures is an important challenge in early stages of program development. Reported graft patency is high in experienced centers, but long-term data remain limited. The steep learning curve, long operative time, high technical complexity, and high capital requirements remain barriers to widespread implementation. Overall, TECAB is a technically demanding minimally invasive revascularization approach with encouraging short- and mid-term results in specialized centers; however, broader adoption remains limited by technical complexity, programmatic demands, and the need for continued multicenter evaluation and structured training pathways.